An anchorage planning strategy with safety and utilization considerations. (October 2015) - Oz, Dindar; Aksakalli, Vural; Alkaya, Ali Fuat; Aydogdu, Volkan
Abstract: Heavy maritime traffic and the subsequent increase in vessel density in anchorages have recently become a focal issue in maritime traffic safety. In this study, we consider the problem of determining the optimal berth locations of incoming vessels in an anchorage area with the goals of maximizing utilization and minimizing the risk of accidents. We introduce novel performance metrics aimed at measuring achievement of these two goals. In this context, we propose a multi-objective optimization strategy and benchmark it against current state-of-the-art anchorage planning algorithms using real-world data as well as Monte Carlo simulations. Our results indicate that the proposed strategy yields much safer berth locations while maintaining similar utilization levels. Abstract : Highlights: We study the problem of determining optimal anchorage positions of incoming vessels. We consider the goals of maximizing utilization and minimizing risk of accidents. We introduce performance metrics aimed at measuring achievement of these goals. We propose a multi-objective anchorage planning strategy. We benchmark it against current state-of-the-art anchorage planning algorithms.